2007
DOI: 10.1021/op7001613
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Process for the Synthesis of the Bcl Inhibitor Obatoclax

Abstract: Recently we created the novel indolylprodigiosin derivative 2 (obatoclax) and demonstrated its ability to antagonize multiple members of the B-cell lymphoma (Bcl) family of antiapoptotic proteins. The compound has shown potent anticancer activity in several animal tumor models. Obatoclax is now in Phase 1b and 2 clinical trials directed against multiple hematologic and solid tumor malignancies. To support its clinical development, a new scalable synthesis was required. Obatoclax has been prepared using a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…Synthesis and anion-binding studies: Compounds 1 a-c were synthesized by using variations on reported procedures (Scheme 1). [10] Briefly, acid-catalyzed condensation of indole-pyrrole aldehyde 6 with assorted pyrroles gave 1 a and analogues 1 b and 1 c in good yields. Small amounts of a symmetrical derivative 2 were also detected in the reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and anion-binding studies: Compounds 1 a-c were synthesized by using variations on reported procedures (Scheme 1). [10] Briefly, acid-catalyzed condensation of indole-pyrrole aldehyde 6 with assorted pyrroles gave 1 a and analogues 1 b and 1 c in good yields. Small amounts of a symmetrical derivative 2 were also detected in the reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…This process has been used by Gemin X to prepare multikilogram quantities of a synthetic prodigiosin analogue, obatoclax, for clinical trials. 33 …”
Section: Total Synthesesmentioning
confidence: 99%
“…8,20–27 A synthetic analogue based on the prodiginine family, obatoclax, was used in multiple phase I and II combination cancer chemotherapy studies. 2833 The quorum sensing control of prodigiosin biosynthesis and medicinal properties of the prodiginines have been previously reviewed. 3,8,24,34,35 …”
Section: Introductionmentioning
confidence: 99%
“…A candidate for earliest patented small molecule inhibitor of Bcl-2 is Obatoclax (GX15-070) (Figure 2D) developed by Gemin X Biotechnologies Inc. from derivatives of the bacterially derived streptorubin B (Daïri et al 2007; Shore and Viallet. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This approach to screen for broad functional inhibition of BH3-only binding led to the development of a true pan-Bcl-2 inhibitor. In similar fashion, Obatoclax (GX15-070) was rationally designed to fit the Bcl-2 BH3-binding domain in competition with pro-apoptotic Bax (Daïri et al 2007). It was developed using structural data obtained from the bacterial derivative Streptorubin B.…”
Section: Introductionmentioning
confidence: 99%